Perceived usefulness of trauma audit filters in urban India: a mixed-methods multicentre Delphi study comparing filters from the WHO and low and middle-income countries. Issue 6 (9th June 2022) - Berg, Johanna; Alvesson, Helle Molsted; Roy, Nobhojit; Ekelund, Ulf; Bains, Lovenish; Chatterjee, Shamita; Bhattacharjee, Prosanta Kumar; David, Siddarth; Gupta, Swati; Kamble, Jyoti; Khajanchi, Monty; Lal, Pawanindra; et al.
Abstract : Objective: To compare experts' perceived usefulness of audit filters from Ghana, Cameroon, WHO and those locally developed; generate context-appropriate audit filters for trauma care in selected hospitals in urban India; and explore characteristics of audit filters that correlate to perceived usefulness. Design: A mixed-methods approach using a multicentre online Delphi technique. Setting: Two large tertiary hospitals in urban India. Methods: Filters were rated on a scale from 1 to 10 in terms of perceived usefulness, with the option to add new filters and comments. The filters were categorised into three groups depending on their origin: low and middle-income countries (LMIC), WHO and New (locally developed), and their scores compared. Significance was determined using Kruskal-Wallis test followed by Wilcoxon rank-sum test. We performed a content analysis of the comments. Results: 26 predefined and 15 new filter suggestions were evaluated. The filters had high usefulness scores (mean overall score 9.01 of 10), with the LMIC filters having significantly higher scores compared with those from WHO and those newly added. Three themes were identified in the content analysis relating to medical relevance, feasibility and specificity . Conclusions: Audit filters from other LMICs were deemed highly useful in the urban India context. This may indicate that the transferability of defined trauma audit filters between similar contexts is high and that these can provide a starting point when implemented as part of trauma quality improvement programmes in low-resource settings.